Psychopathy and Protective Behavioral Strategies: PBS Mediates the Relationships between Primary and Secondary Psychopathy and Alcohol Consumption and Problems. Issue 3 (3rd July 2022) - Kramer, Matthew P.; Peterson, Roselyn; Willis, Emy A.; Leary, Angelina V.; Magri, Tatiana; Cora, Jessica L.; Dvorak, Robert D.
Abstract : Objective : The most common conceptualization of psychopathy is a two-factor model of primary psychopathy and secondary psychopathy. Primary psychopathy consists of interpersonally abusive behavior, and callousness. Secondary psychopathy includes impulsive and risky decision making. Past research has found that psychopathy is related to negative outcomes, including increased alcohol consumption and problems, and is inversely related to harm reduction behaviors. Protective behavioral strategies (PBS), behaviors designed to reduce alcohol consumption and associated problems, may mediate the relationship between psychopathy and alcohol pathology. The current study examined the relationship between psychopathy, each subtype of PBS use (serious harm reduction (SHR), manner of drinking (MD) and stopping/limiting drinking (SLD)), alcohol consumption, and alcohol problems. Method : Participants were n = 967 (61.22% female) college students. Participants completed measures assessing psychopathy, PBS use, alcohol consumption, and alcohol problems. A path analysis was conducted to examine the relationships between psychopathy, subtypes of PBS, and alcohol consumption and problems. Results : Results indicated an inverse relationship between primary psychopathy and both SHR PBS and MD PBS, while secondary psychopathy was inversely associated with all three PBS subtypes. SHR PBS was inversely associated with alcohol problems while MD PBS was inversely associated with alcohol consumption. Conclusion : These findings suggest specific PBS subtypes mediate the relationship between primary and secondary psychopathy and alcohol consumption and problems. It may be clinically pertinent to consider targeting PBS use, such as with motivational interviewing, when working with patients exhibiting psychopathy traits. Future research should consider these findings when examining alcohol use.